Pengaruh Marketing Public Relation Terhadap Word Of Mouth Communication (Studi Pada Objek Wisata Taman Safari Indonesia Bogor) - Sukmadi, S.; Usman, Maman (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2017)
This research was conducted to .find (1) the application of marketing public relations, (2) communication word of mouth on the attractiveness of Taman Safari Indonesia, (3) the influence of marketing public relations for word of mouth communication. The method used is quantitative with explanatory research type, which explains the causal relationship between the independent variables on the dependent variable through hypothesis testing. This type of research consists of descriptive and verification conducted through data collection in the field Data collection methods used in the form of a questionnaire measuring instrument method research is conducted with a sample of 46 tourists. This study uses a descriptive analysis of the frequency and method of simple linear regression. The results showed that (1) the relationship public marketing undertaken by manager Taman Safari Indonesia has done well, through publications, events, sponsorship, news, speeches, public service and media activity identity, (2) communication word of mouth carried by tourists so that it can help disseminate information on attractions quickly. This study found that the tourist attractions are also provided recommendations, saying positive things and encourage and influence others to visit the attractions are concerned. (3) There is a significant positive effect between marketing and public relations for the communication word of mouth. This indicates a better marketing, Public Relations better than word of mouth communication about the appeal.